Involvement of ELAV RNA-binding proteins in the post-transcriptional regulation of HO-1 - Amadio, Marialaura; Scapagnini, Giovanni; Davinelli, Sergio; Calabrese, Vittorio; Govoni, Stefano; Pascale, Alessia (Frontiers in Cellular Neuroscience, 2015)
Heme oxygenase-1 (HO-1) is an inducible rate-controlling enzyme of heme catabolism. The cytoprotective function of HO-1 activity has been verified in multiple studies, and together with its by-products is considered a key component of the cellular stress response. The transcriptional induction of HO-1 has been largely studied in response to multiple forms of stressful stimuli but our understanding of HO-1 post-transcriptional control mechanisms in neuronal cells is currently lacking. In the present report we show the involvement of the RNA-binding proteins ELAV in the regulation of HO-1 gene expression. Our study demonstrates a specific binding between HO-1 mRNA and ELAV proteins in a human neuroblastoma cell line treated with hemin. Clarifying the induction of HO-1 expression at post-transcriptional level may open therapeutic perspectives for treatments associated with the modulation of HO-1 expression.